Monitoring for and Management of Endocrine Dysfunction in Adrenoleukodystrophy - Isha Kachwala; Molly O. Regelmann (MDPI AG, 2022)
Adrenoleukodystrophy (ALD) is a peroxisomal disorder affecting the nervous system, adrenal cortical function, and testicular function. Newborn screening for ALD has the potential to identify patients at high risk for life-threatening adrenal crisis and cerebral ALD. The current understanding of the natural history of endocrine dysfunction is limited. Surveillance guidelines for males with ALD were developed to address the unpredictable nature of evolving adrenal insufficiency. Early recognition and management of adrenal insufficiency can prevent adrenal crisis. While testicular dysfunction in ALD is described, the natural history and complications of low testosterone, as well as the management, are not well described.